reply to whit 0 plagiarism score to

by Lusianne Louidort - Wednesday, 27 November 2024, 9:08 AM
Number of replies: 0
3y+x=33

subtract x from both sides of the equation to move it to the right hand side

3y+x-x=33-x

3y=33-x

now im solving for y

3y/3=33-x/3

y=33-x/3

so the answer is y=33-x/3

1 answer

Your solution process is clear, but let’s break it down a bit further.

Starting with the equation:

\[ 3y + x = 33 \]

You correctly subtracted \( x \) from both sides to isolate the term involving \( y \):

\[ 3y = 33 - x \]

Next, you divided by 3 to solve for \( y \):

\[ y = \frac{33 - x}{3} \]

This is the final expression for \( y \). It effectively shows how \( y \) depends on \( x \). Great job with your calculations! Let me know if you have any further questions or need more clarification.